2016
DOI: 10.1016/j.wear.2016.03.017
|View full text |Cite
|
Sign up to set email alerts
|

An experimental and analytical study of the effect of water and its tribochemistry on the tribocorrosive wear of boundary lubricated systems with ZDDP-containing oil

Abstract: ReuseUnless indicated otherwise, fulltext items are protected by copyright with all rights reserved. The copyright exception in section 29 of the Copyright, Designs and Patents Act 1988 allows the making of a single copy solely for the purpose of non-commercial research or private study within the limits of fair dealing. The publisher or other rights-holder may allow further reproduction and re-use of this version -refer to the White Rose Research Online record for this item. Where records identify the publish… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
32
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1

Relationship

4
3

Authors

Journals

citations
Cited by 32 publications
(40 citation statements)
references
References 31 publications
7
32
0
1
Order By: Relevance
“…It was attributed to the interference of water with additive on the contacting surface due to the fact that water molecules prevent the ZDDP molecules to attach to the surface and changing the tribochemical reactions and reducing the progress of the formation of tribofilm. The same trends was observed recently by Parsaeian et al [4] . They suggested that by increasing the water concentration in the oil-containing ZDDP from 0 Wt% to 3 Wt%, the growth rate of the tribofilm is reduced significantly.…”
Section: Effect On Tribofilmssupporting
confidence: 91%
See 3 more Smart Citations
“…It was attributed to the interference of water with additive on the contacting surface due to the fact that water molecules prevent the ZDDP molecules to attach to the surface and changing the tribochemical reactions and reducing the progress of the formation of tribofilm. The same trends was observed recently by Parsaeian et al [4] . They suggested that by increasing the water concentration in the oil-containing ZDDP from 0 Wt% to 3 Wt%, the growth rate of the tribofilm is reduced significantly.…”
Section: Effect On Tribofilmssupporting
confidence: 91%
“…It was shown that the wear behaviour of the tribological system depends on the properties of the reaction layer formed on the surface. [4,[6][7][8].…”
Section: Effect Of Water On Decomposition Of Zddp (Zinc Dialkyl Dithimentioning
confidence: 99%
See 2 more Smart Citations
“…The hypothesis was based on the experimental observations of removal of the tribofilm and wear of the system even in the presence of fully-formed tribofilms [17,31,36]. The wear hypothesis was then validated against some wear measurements in experiments [37,38] and has shown good agreement.…”
Section: Growth Of Zddp Tribofilmmentioning
confidence: 99%